Do social accountability approaches work? A review of the literature from selected low- and middle-income countries in the WHO South-East Asia region - Naher, Nahitun; Balabanova, Dina; Hutchinson, Eleanor; Marten, Robert; Hoque, Roksana; Tune, Samiun Nazrin Bente Kamal; Islam, Bushra Zarin; Ahmed, Syed Masud (Oxford Academic, 2022)
This article was published in Health Policy and Planning by Oxford Academic [ The Author(s) 2020. Published by Oxford University Press in association with The London School of Hygiene and Tropical Medicine] and the definite version is available at: https://doi.org/10.1093/heapol/czaa107 The Journal's website is at: https://academic.oup.com/heapol/article/35/Supplement_1/i76/5960441